Analysis of Radiation Intensity and Sunshine Duration in the Karst Area of Maros TN Bantimurung Bulusaraung South Sulawesi During Solstice Phenomenon - Muhammad Arsyad; Rihan Muhammad Alghifari; Agus Susanto; Pariabti Palloan; Sulistiawaty (Postgraduate, University of Mataram, 2021)
This study aims were to analyze the profile of radiation intensity and sunshine duration in the karst area of Maros TN Bantimurung Bulusaraung, South Sulawesi during solstice phenomenon in the period 2011-2020. In addition, radiation intensity and sunshine duration in the same area were also measured. A Pearson correlation shows that the intensity of solar radiation and the sunshine duration have a bimodal pattern. The average radiation intensity during the 2011-2020 solstices in June and December was 1.193 Â and 1.249 , respectively. Whereas the percentage of sunshine duration in June and December reached 54% and 35%, respectively. The results of the Pearson correlation analysis of the relationship between radiation intensity and sunshine duration in June were 0.722, while in December, it was 0.717. The interpretation results show that the two parameters have a strong correlation and have a close relationship